The Effect Of Single Point Cup Therapy On Blood Pressure In Hypertension Patients At Campaka Arum Health Center - Dede Nur Aziz Muslim; Somantri Somantri; Haerul Imam (International Journal of Quantitative Research and Modeling, 2023)
The highest prevalence in the world is hypertension because this disease is not controlled optimally. Hypertension can be overcome by pharmacological treatment such as drugs that are diuretic, sympathetic and vasodilator. As well as nonpharmacological treatment with weight loss, regular exercise, low salt consumption, low fat and complementary therapies. One of the effective complementary therapies to treat hypertension is cupping therapy. The cupping point used, namely the al-kahil point, serves to prevent an increase in blood pressure. The purpose of this study was to determine the effect of one-point cupping therapy on blood pressure in patients with hypertension at the Cempaka Arum Health Center. The research method used a preexperiment with a one group pre-test- post-test approach. The research population is hypertension sufferers at the Cempaka Arum Health Center with a sample of 41 respondents. The instruments used are sphygnomanometer and stethoscope, as well as an assessment sheet. Data analysis using the Wilcoxon test. The results of statistical tests showed a decrease in blood pressure with a difference of 15,42 (systolic) and 11.71 (diastole). From the Wilcoxon test results obtained p-value 0.000 or p <0.005 so that H0 is rejected and Ha is accepted. It can be concluded that there is an effect of one-point cupping therapy on blood pressure in patients with hypertension at the Cempaka Arum Health Center. It is hoped that this therapy can be included in the list of alternative therapies to treat hypertension at the Cempaka Arum Health Center.